Directions of the state policy of technological development of the mining and metallurgical complex of Kazakhstan - Kabdybay, A.K.; Kenzhebekov, N.D.; Syzdykova, D.I.; Ulybyshev, D.N.; Zhailauov, Ye.B. (KU publ., 2020)
Object: The purpose of the research is to determine the priorities of Kazakhstan's technological policy aimed at modernizing and developing high-tech production in the domestic metallurgical complex. Methods: The research used the method of system analysis, the method of collecting secondary information, the method of structuring goals. Results: As the main results, it is necessary to highlight the assessment of the state and definition of the role of the metallurgical complex in the economic potential of the republic, based on the definition of development priorities, recommendations were given on the structural and technological reform of metallurgy in Kazakhstan. It should be noted that with a high share of the export component in the sales structure of metallurgical enterprises and a constant shortage of metal products in the domestic market, domestic enterprises do not have a strong motivation to expand the range and master new materials. Conclusions: In our opinion, breakthrough technologies from the existing innovation system should not be expected in the near future, the transfer of technologies is difficult due to existing counterparties: foreign investments of large transnational corporations are aimed at developing the raw material base and attracting mining capacities. In this regard, state policy should be aimed primarily at the complexity and rationality of the use of natural resources. To ensure a more complete use of the production capacities of the existing enterprises, one of the ways to replenish the retired capacities is to bring into operation poor off-balance ores, as well as re-development of previously worked out areas, reactivation of protective pillars and recovery of ores written off as losses.
Қазақстанның кен-металлургиялық кешенінің технологиялық дамуының мемлекеттік саясатының бағыттары
Направления государственной политики технологического развития горно-металлургического комплекса Казахстана
Keywords: mining and metallurgical complex; metallurgical treatment; modernization; rational use of mineral resources; technological policy; competitiveness of the metallurgical industry; technological structure